Experiences and perceptions of family members of emergency first responders with post-traumatic stress disorder: a qualitative systematic review protocol. Issue 7 (2nd July 2021) - May, Karen; Van Hooff, Miranda; Doherty, Matthew; Iannos, Marie
ABSTRACT: Objective: The objective of this review is to understand the perceptions and experiences of family members of emergency first responders with post-traumatic stress disorder. Introduction: Research indicates that rates of post-traumatic stress disorder in emergency first responders are approximately double civilian rates; however, little is known about the effects of post-traumatic stress disorder on family members. This review seeks to identify qualitative research on families' experiences and perceptions. Inclusion criteria: This review will consider all studies of family members of current or former emergency first responders with diagnosed or undiagnosed post-traumatic stress disorder of any level of severity. All possible familial configurations and family members will be considered, including nuclear, separated, and blended families, of a current or former emergency first responder. There will be no age restrictions on emergency first responders or their family members, or limitations on recency of service. Emergency first responders may include police, ambulance workers, paramedics, firefighters, or rescue personnel, with no restriction on geographic location. Methods: The databases to be searched will include PubMed, PsycINFO, Embase, CINAHL, PTSDpubs, and Scopus, as well as handsearching of relevant journals. Unpublished studies and gray literature will be searched via PTSDpubs and OpenGrey. The search will aim to find English-language publications with no time limits. Titles and abstracts will be reviewed and then full texts, all screened by two independent reviewers against the inclusion criteria. Any conflicting views will be resolved by discussion or a third reviewer. Results will be critically appraised for methodological quality. Data extraction results will be synthesized and evaluated for credibility and dependability. Systematic review registration number: PROSPERO CRD42020196605